A política cultural da União Europeia e a lógica de protecção das diversidades culturais dos estados-membros - Laureano, Abel (2014)
The European Union's integration imperatives lead naturally to the desirability of the greatest possible freedom in intra- Community movements of people and goods. On the other hand, the European Union's Member States represent an authentic multicultural mosaic, which turns difficult such a freedom. Facing this background, the European Union began by adopting a restraint posture, along which came to introduce, however, from a certain time on, active elements of safeguarding and promoting a European common culture, thus creating, nevertheless, a theoretically complex and practically tricky framework.